Correlation Analysis of Mechanical Vibrations Produced by Electrical Equipment and Presence of Discomfort and Pain of Workers of Electronics Industry of Mexicali, Mexico - González, Yanet Villarreal; Zepeda, Pedro Alberto Escárcega; González, Carlos Raúl Navarro; Corona, Ana Laura Sánchez; Robledo, Verónica Arredondo; Hernandez, Juan Gabriel Lopez; Badilla, Gustavo Lopez (New Ideas Concerning Science and Technology Vol. 5, 2021)
This paper shows an analysis of the possibility of having a negative effect on the health of workers in industrial plants, where there are industrial equipment and machines that generate vibrations at different frequency levels. The investigation consisted of developing an evaluation of a worker using a device that has the function of placing screws (screwdriver) and removing screws (screwdriver) in an industrial company that manufactures laptop computers. This industry located in the city of Mexicali, located in the northwest of Mexico, is a microindustry of electronics sector as Small and Medium Enterprises (SMES) of 60 workers supports a large company of 500 workers, located in this same city and manufactures enormous quantities of laptop computers and generates about 25% defects of its total production. The SME evaluated, elaborates activities of reception, repair and shipment of laptop computers to the large industrial plant. The scientific study was made 2018 to 2019.